Satisfaction of Restituted Farms Beneficiaries with Performance of Farms in Waterberg District, South Africa - Tjale, Malose Moses; Mwale, Marizvikuru; Kilonzo, Beata M. (AGRARIS: Journal of Agribusiness and Rural Development Research, 2020)
South African government guided by the Restitution of Land Rights Act 22 of 1994, implemented land restitution as one of the pillars of land reform programme. The mandate was to promote land ownership and equality between white and black people. This study determined the extent to which farm beneficiaries are satisfied with the performance of the restituted farms in Waterberg District. Quantitative approach was used to examine closed-ended data using stratified random sampling procedure. Interviews, photo-voice and non-participatory observation methods were additionally used to collect data through qualitative approach. The Statistical Package for the Social Sciences (SPSS version 25) was used to compute descriptive statistics and cross-tabulations while content analysis was used for the qualitative data. The study revealed that participation in the restituted farms was dominated by males (73.0 %). About 77 % of the farm beneficiaries were not satisfied with the performance of the farms and 60.5 % of them confirmed that their livelihoods were not changed due to lack of farm income. Moreover, (90.3 %) reported that farms did not create job opportunities for beneficiaries. It is recommended that intervention strategy, be implemented to enhance farm performance that will satisfy farm beneficiaries.